2005
DOI: 10.1590/s1807-59322005000300004
|View full text |Cite
|
Sign up to set email alerts
|

Edema and Malignancy in Meningiomas

Abstract: These results suggest that the degree of edema as revealed by computer tomography and magnetic resonance imaging can be an important clinical predictive factor for the histological grade of the meningioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 46 publications
2
12
1
2
Order By: Relevance
“…19 that the degree of peritumoral brain edema is more significant in atypical and malignant meningiomas than in typical meningiomas. 23 In our study, 59.3% of benign and 81.3% of atypical/malignant meningiomas were associated with peritumoral brain edema; however, the difference was not statistically significant. These findings and discrepancies between studies might reflect the combination of multiple factors (including histological subtypes) contributing to peritumoral brain edema, which have yet to be determined.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…19 that the degree of peritumoral brain edema is more significant in atypical and malignant meningiomas than in typical meningiomas. 23 In our study, 59.3% of benign and 81.3% of atypical/malignant meningiomas were associated with peritumoral brain edema; however, the difference was not statistically significant. These findings and discrepancies between studies might reflect the combination of multiple factors (including histological subtypes) contributing to peritumoral brain edema, which have yet to be determined.…”
Section: Discussioncontrasting
confidence: 58%
“…Many factors have been proposed regarding the development and degree of meningioma-induced brain edema, including tumor size, histological subtypes, tumor vascularity, venous stasis, type of arterial supply (pial or dural predominance), sex hormone receptors, effect of vascular endothelium growth factor, secretory activity, ischemia and true brain invasion. [20][21][22][23][24][25][26][27][28][29] Some investigators have found no significant correlation between histological subtypes of meningiomas and peritumoral brain edema. 19 that the degree of peritumoral brain edema is more significant in atypical and malignant meningiomas than in typical meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…7,15,23,31 Nakano et al 26 reported that the invasive pattern of tumor-brain interface-including irregular tumor margins, disappearance of the peritumoral rim, and hyperintensity of the tumor on T2-weighted imagingwas associated with meningioma-related brain edema. However, several studies showed no significant correlation between histological subtypes of meningiomas and peritumoral brain edema.…”
Section: Discussionmentioning
confidence: 99%
“…The edema was classified according to the slightly longer T2 signal range surrounding the lesions on the T2WI, grade 0: no edema or only a ring around the halo, grade I: the edema spreads along the white fiber, grade 2: the edema involving the entire hemisphere of the brain (Matttei et al, 2005;Veillon et al, 2008).…”
Section: Image Analysismentioning
confidence: 99%